2018
DOI: 10.20944/preprints201807.0210.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hydrological Modeling in Tropical Regions via TopModel. Study Case: Central Sector of the Middle Magdalena Valley - Colombia

Abstract: Hydrological modeling allows us to make a comprehensive assessment of the interaction between dynamics of the hydrological cycle, climate conditions, and land use. These modeling results are relevant in water resources management field. We use TopModel (TOPography based hydrological MODEL for the hydrological 15 modeling of an area of 17 000 km 2 in the Middle Magdalena Valley (MMV), a tropical basin located in Colombia.This study is located in the intertropical convergence zone (ITCZ) which is characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Hydrological models such as the hydrologic modeling system (HEC-HMS) [7,8], the Australian water balance model (AWBM) [9], the soil moisture accounting and routing (SMAR) model [10], the topography-based hydrological model (TOPMODEL) [11,12] and the soil and water assessment tool (SWAT) [13] are useful for simulating the runoff from ungauged catchment based on the data availability and complexity of the hydrological system. Many studies have demonstrated that SWAT is an effective and promising tool to use for simulating flows and sediments for large-scale watersheds and complex basins with different land uses and various soil types (Access et al [14], Brouziyne et al [15], Palani et al [16], Amatya et al [17], and Tri et al [18], among others).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrological models such as the hydrologic modeling system (HEC-HMS) [7,8], the Australian water balance model (AWBM) [9], the soil moisture accounting and routing (SMAR) model [10], the topography-based hydrological model (TOPMODEL) [11,12] and the soil and water assessment tool (SWAT) [13] are useful for simulating the runoff from ungauged catchment based on the data availability and complexity of the hydrological system. Many studies have demonstrated that SWAT is an effective and promising tool to use for simulating flows and sediments for large-scale watersheds and complex basins with different land uses and various soil types (Access et al [14], Brouziyne et al [15], Palani et al [16], Amatya et al [17], and Tri et al [18], among others).…”
Section: Introductionmentioning
confidence: 99%
“…During the Mesozoic, the central and eastern Andes Mountain ranges were elevated, resulting in the formation of the MMV basin. It consists of sedimentary strata from the Cretaceous Period over a Jurassic igneous metamorphic basement with an average thickness of 8500 m [50][51][52][53] . To the south, there are outcrops of the Real Group, a Neogene formation whose thickness varies from 450 to 3500 m. In the north, there are Quaternary deposits outcrops underlying Real Group.…”
Section: Hydrogeological Contextmentioning
confidence: 99%
“…Dynamic‐TOPMODEL of Beven and Freer (2001) relaxed both of the above assumptions by allowing subsurface storage of individual HSUs to vary locally and independently of both the catchment average storage and TI, by incorporating a time‐dependent kinematic wave solution to the subsurface flow. However, since its introduction 20 years ago, and despite significantly improving catchment representation, the original steady‐state version has remained the preferred choice (albeit sometimes with modifications/improvements) (Arenas‐Bautista et al., 2018; Fu et al., 2018; Gil & Tobón, 2016; Jeziorska & Niedzielski, 2018; J. Wang et al., 2020; Lane & Milledge, 2013; Li et al., 2019; Mukae et al., 2018; Park et al., 2019; Rogelis et al., 2016; Xue et al., 2018; Zhang et al., 2016). Aside from the considerable additional complexity in numerical implementation of the dynamic versus the steady‐state version, the lack of momentum in transitioning is most likely due to the substantially slower runtimes, making the dynamic version much less attractive for calibration purposes.…”
Section: Introductionmentioning
confidence: 99%